Cationic and Anionic Antimicrobial Agents Co-Templated Mesostructured Silica Nanocomposites with a Spiky Nanotopology and Enhanced Biofilm Inhibition Performance - Song, Yaping; Sun, Qiang; Luo, Jiangqi; Kong, Yueqi; Pan, Bolin; Zhao, Jing; Wang, Yue; Yu, Chengzhong (Nano-Micro Letters, 2022)
Silica-based materials are usually used as delivery systems for antibacterial applications. In rare cases, bactericidal cationic surfactant templated silica composites have been reported as antimicrobial agents. However, their antibacterial efficacy is limited due to limited control in content and structure. Herein, we report a “dual active templating” strategy in the design of nanostructured silica composites with intrinsic antibacterial performance. This strategy uses cationic and anionic structural directing agents as dual templates, both with active antibacterial property. The cationic-anionic dual active templating strategy further contributes to antibacterial nanocomposites with a spiky surface. With controllable release of dual active antibacterial agents, the spiky nanocomposite displays enhanced anti-microbial and anti-biofilm properties toward Staphylococcus epidermidis. These findings pave a new avenue toward the designed synthesis of novel antibacterial nanocomposites with improved performance for diverse antibacterial applications. Highlights: 1 A ‘dual active templating’ strategy is firstly reported, using cationic and anionic bactericidal agents as co-templates for the preparation of antibacterial silica nanocomposite with spiky nanotopography. 2 The spiky nanocomposite exhibited enhanced antibacterial and biofilm inhibition performance, compared to pure antimicrobial cationic agent templated smooth silica nanocomposite.